EFFECTIVENESS OF PAMEKASAN CALL CARE PROGRAM IN EMERGENCY HEALTH SERVICES - Mohammad Bustanol Husein; Indah Febriyanti Faizal; Erina Saputri (DIA: Jurnal Administrasi Publik, 2026)
Public service innovation in the health sector is an important effort by local governments to improve community welfare and ensure rapid response to emergency situations. One of the innovations implemented by the Pamekasan Regency Government is the Pamekasan Call Care (PCC) program, which functions as an integrated emergency health service operating 24 hours. However, the implementation of this program still faces several challenges, such as limited public awareness, communication barriers, and operational constraints. This study aims to analyze the effectiveness of the Pamekasan Call Care program as an emergency service in Pamekasan District. The research uses a qualitative descriptive approach to explore the effectiveness of the program based on field conditions. Data were collected through interviews, documentation, and observations involving key stakeholders such as the PCC coordinator, local government officials, and community members who utilized the service. The analytical framework used in this study refers to the program effectiveness indicators proposed by Budiani (2007), namely program target accuracy, program socialization, program goal achievement, and program monitoring. Data analysis was conducted using the interactive model developed by Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings indicate that the effectiveness of the Pamekasan Call Care program has not been fully achieved. Several indicators such as program target accuracy, socialization, and monitoring have not been implemented optimally. The lack of continuous socialization and limited operational facilities have contributed to the low level of public awareness regarding the program. Therefore, improving infrastructure, strengthening inter-agency coordination, and enhancing program monitoring are necessary to increase the effectiveness of PCC services. Strengthening these aspects is expected to improve the quality of emergency health services and expand the benefits of the program for the community.